Protective Effect of Tetramethylpyrazine on Myocardial Ischemia-Reperfusion Injury. (23rd July 2014) - Qian, Weidong; Xiong, Xingjiang; Fang, Zhuyuan; Lu, Haiting; Wang, Zhensheng
Abstract : Myocardial ischemia-reperfusion injury (MIRI) is a common pathological and physiological phenomenon. Tetramethylpyrazine is the extract of the traditional Chinese medicine Chuanxiong, which can exert protective effects on MIRI in multiple ways. This paper reviewed the current research progress and evidence about the cardiovascular effects of tetramethylpyrazine, which included protecting mitochondria and improving energy metabolism, scavenging oxygen free radicals (OFRs) to inhibit lipid peroxidation, attenuating calcium (Ca 2+ ) overload and maintaining Ca 2+ homeostasis in cells, inhibiting apoptosis and protecting myocardial cells, interfering with the inflammatory reaction and mitigating cell injury, interfering with cell signaling pathways, and improving function of endothelial cells and protecting myocardial cells. However, further rigorously designed randomized controlled trials are warranted.